Urbanization induced land use/land cover change and its impact on land surface temperature in Bhubaneshwar city, India - Singh, Kiran Kumari; Parida, Madhusmita; Jasrotia, Garima (Acta Geographica Debrecina Landscape & Environment series, 2025)
The study was conducted in Bhubaneswar City, the capital of the Indian state of Odisha. The impact of the increase in surface temperature on the city was studied by retrieving LST, Normalized Difference Vegetation Index (NDVI), and Normalized Difference Vegetation Index (NDBI) values of Bhubaneswar using Landsat 5 and Landsat 8 data for 2001, 2011, and 2021. The surface urban heat island (SUHI) effect was also studied to identify temperature changes and hotspots in the city. There was a rise of 3.93℃ and 1.55℃ in the maximum and minimum LST in Bhubaneshwar city from 2001 to 2021. The heating effect of the built-up and cooling effect of vegetation was ascertained through correlation analysis between LST and NDBI (positive) and between LST and NDVI (negative). The results of this study will help the government and urban planners to identify heat stress and vulnerable areas, thereby contributing to better monitoring and future planning of the city. Thus, this will lead to efficient heat strategies and action plans such as developing green spaces in and around the city.